KEARIFAN LOKAL MASYARAKAT DALAM PELESTARIAN LAHAN GAMBUT DI KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Megawati, Megawati; Zainal, Sofyan; Burhanuddin, Burhanuddin (Universitas Tanjungpura, 2020)
Community local wisdom of peatlands conservation in Punggur Kecil villages is one form of community life culture in peserving peatlands for generation to generation. The purpose of this study is to examine the forms of local wisdom in preserving peatlands, analyzing the obstacles faced by the community in maintaining local wisdom as a supporter of peatland sustainability and analyzing and describing the community to have a role in peatland management. This research was condected in Punggur Kecil village Sungai Kakap sub-district Kuburaya Regency. This research was carried out for 2 weeks effectively in the field. The tools used include writing instruments, questionnaires, calculators, recording devices, cameras, and maps of research locations. The method used is a survey and observation method with direct interview techniques. Sampling is done by using purposive sampling. Based on the results of farming research is part of the local wisdom of Punggur Kecil village community which is also part of their cultural identity in addition to of course as an effort to meet food and economic needs of the family. The form of local wisdom of the people besides farming, namely by making ditches or regulating water systems. Land preparation by peasants on peatland land in traditional culture of the village community using long type machetes. Currently the biggest obstacle to peat is drainage and fires which are usually accompanied by forest conversion. Based on the results of field observations and discussions from the results of reserch conducted in general, the village community managed peatlands well. The results of the research conducted showed that all existing land management models use a mixed system. In the rice fields of the community, they combine rice plants with other holiculture plants such as chili, spinach, yams, leeks, bananas and other types of plants such as coconut, langsat and durian. Local community needs is obtained from agricultural products for their lively hood.Keywords : Peatlands, Peatland conservation, Punggur Kecil Villages.